PMSM Position Sensorless Control Based on Improved Second-Order SOIFO - Ge Song; Hongyu Ni; Wenyuan Wang; Wenxu Yan (World Electric Vehicle Journal)
Due to detection errors, motor parameter deviations, and other uncertainties, traditional motor flux estimation models suffer from the complications of DC bias and high-order harmonics. To address these issues, two flux observers, the second-order generalized integrator flux observer (SOIFO) and the second-order SOIFO, are designed for position sensorless control of permanent magnet synchronous motors (PMSMs). The position sensorless control of PMSMs based on an improved second-order SOIFO is proposed in this paper. The proposed method enhances the frequency-locked loop (FLL) in the observer by introducing a double-axis frequency-locked loop (DFLL), which improves the dynamic performance and disturbance rejection capability of the flux observer. By replacing FLL with DFLL for angular frequency estimation, the method effectively eliminates second-harmonic interference while reducing estimation delays, leading to faster and more accurate rotor position estimation in the second-order SOIFO. Additionally, the improved observer demonstrates enhanced robustness against disturbances, ensuring more stable position sensorless control. The effectiveness of the proposed approach is validated through both simulations and experimental comparisons.